2021
DOI: 10.18805/ijar.b-4700
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seasons on Physiological Responses in Sahiwal and Crossbred Cows

Abstract: Background: Growing demand for improving milk production and rising temperatures due to global warming has increased the thermal load on dairy animals. Physiological parameters such as respiration rate and body temperature mainly determine the adaptability of animals to climate stress. During genetic adaptation, Bos indicus cattle have acquired thermo tolerant genes and when exposed to heat stress conditions, the Bos indicus cattle have lower respiration rates and rectal temperatures than Bos taurus animals. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This condition forces animals to maintain a constant body temperature (homeostasis) with thermoregulation mechanisms (Terrien et al, 2011;Mota-Rojas et al, 2021;Renaudeau et al, 2012) to remove excess heat from the body. 2021), who reported that exercised Bali cattle had higher rectal temperatures between 39.16-40.06 o C. Prasanna et al (2022) reported Sahiwal and Sahiwal cross cattle had higher average rectal temperatures during summer than other seasons, which could be due to the excessive heat production due to the increased metabolic rate.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
See 1 more Smart Citation
“…This condition forces animals to maintain a constant body temperature (homeostasis) with thermoregulation mechanisms (Terrien et al, 2011;Mota-Rojas et al, 2021;Renaudeau et al, 2012) to remove excess heat from the body. 2021), who reported that exercised Bali cattle had higher rectal temperatures between 39.16-40.06 o C. Prasanna et al (2022) reported Sahiwal and Sahiwal cross cattle had higher average rectal temperatures during summer than other seasons, which could be due to the excessive heat production due to the increased metabolic rate.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…Animals that have increased respiration rates do not necessarily indicate that they have been able to maintain a stable body temperature, but rather that the animal has overheated and is trying to restore its body heat balance (Ganaie et al, 2013). Low respiration rates in hot environments indicate a greater tolerance (Prasanna et al, 2022). The normal respiration rate for beef cattle, according to Abdisa ( 2017) is 25-30 breaths/min.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%